Analysis of High Level Thinking Skills, Character and Skills of Science Process of High School Students in Project Based Learning - Wahyu Sejati, Dwi Jayanti; Isnaeni, Wiwi; Saptono, Sigit (Universitas Negeri Semarang, 2021)
This study aims to analyze higher order thinking skills, character, and science process skills of high school students on plant tissue material through the Project Based Learning (PPA) model. This research method uses Pre-Experimental Designs. This research was conducted in Muhammadiyah 1 Karanganyar high school. The research sample used was 78 students. The instruments used were multiple choice questions and observation sheets. Student learning outcomes data were analyzed using the N-Gain technique and the minimal classical completeness test to determine higher order thinking skills (HOTS). The results showed that the Project Besed Learning (PjBL) Model was effective in improving students' high-order thinking skills (HOTS) with an average N-Gain of 0.52 in the